ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PRACTICES IN THE HOSPITALITY SECTOR OF SAUDI ARABIA: LITERATURE REVIEW - Mohammed Hassan Mohammed Alhejaili; Muhammad Ahmad (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
The Saudi government’s Vision 2030 has identified tourism as a crucial factor in the nation’s economic and cultural advancement, recognizing its role as a primary catalyst for change. Although numerous studies have assessed ESG practices by examining various practices identified in the literature, a notable gap exists in the evaluation of ESG practices within hotels in Saudi Arabia. This oversight underscores the necessity for more comprehensive and detailed ESG practices that can effectively measure and enhance the influence of the hotel sector. This research aims to identify the most relevant strategies for measuring Environmental, Social, and Governance (ESG) factors in Saudi hotels, to ascertain the context of the studies, and to highlight opportunities and future trends within the hotel sector. The articles included in this review study were published between 2020 and 2024. It offers a comprehensive analysis of the present state of environmental, social, and governance (ESG) evaluation in Saudi Arabia’s hotel sector. The discussion was focused on the current issues faced in the discipline and the available research prospects within the topic.